2006
DOI: 10.1021/bm060252d
|View full text |Cite
|
Sign up to set email alerts
|

Gelatinization of Starch in Excess Water:  Beyond the Melting of Lamellar Crystallites. A Combined Wide- and Small-Angle X-ray Scattering Study

Abstract: The gelatinization of waxy rice, regular rice, and potato starch suspensions (66% w/w moisture) was investigated by real-time small-angle X-ray scattering (SAXS) and wide-angle X-ray diffraction (WAXD) during heating and by fast ramp differential scanning calorimetry (DSC). The high-angle tail of the SAXS patterns suggested the transition from surface to mass fractal structures in the DSC gelatinization range. Amylose plays a major role in determining the dimensions of the self-similar structures that develop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
52
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(63 citation statements)
references
References 48 publications
9
52
1
1
Order By: Relevance
“…The results obtained (Table 1) are smaller than those previously determined for rice and potato starches (Vermeylen et al, 2006) and may be an artefact of the extrapolation procedure adopted here. Nevertheless, we interpret these results as a consequence of enzymatic trimming (Ball et al, 1996;Mouille et al, 1996) required to generate order in the amorphous lamella for subsequent synthesis of the crystalline lattice, as illustrated in Fig.…”
Section: Saxs Analysiscontrasting
confidence: 80%
“…The results obtained (Table 1) are smaller than those previously determined for rice and potato starches (Vermeylen et al, 2006) and may be an artefact of the extrapolation procedure adopted here. Nevertheless, we interpret these results as a consequence of enzymatic trimming (Ball et al, 1996;Mouille et al, 1996) required to generate order in the amorphous lamella for subsequent synthesis of the crystalline lattice, as illustrated in Fig.…”
Section: Saxs Analysiscontrasting
confidence: 80%
“…The endothermic transition of native starch in the DSC profile represents the incomplete gelatinization of starch granules under low water conditions (starch:water ratio 1:2) . Substantial residual crystallinity and lamellar organisation remain after native starch granules are allowed to swell in limited water (Jenkins & Donald, 1998;Vermeylen et al, 2006). In a separate experiment, the swelling of alkali-treated starch granules was also shown to be incomplete at a starch:water ratio of 1:2 (data not shown).…”
Section: Effect Of Alkaline Treatment On Starch Functionalitymentioning
confidence: 91%
“…4 that the lamellar peak disappeared rapidly (as early as 2 min), which meant that the crystalline lamellar structure was damaged by shear. The kneading process is different from a general gelatinization process where heating (Vermeylen et al, 2006;Zhang et al, 2015), microwave heating (Fan et al, 2013(Fan et al, , 2014, or ultra-high hydrostatic pressure (Yang et al, 2016a) was applied. The in-situ SAXS data showed that the change under mechanical kneading was a more gradual process.…”
Section: Molecular Size Distribution Of Debranched Starch During Shearmentioning
confidence: 99%